Administration and the limits of democracy: The space of 19th century American governance. - Stivers, Camilla (2011)
Most administrative theory addresses how to make practice effective by means of abstract concepts: laws, regulations, and theories. Recent history is littered with examples of government's failure - despite plans and protocols - to cope with disastrous events, calling into question continuing pursuit of a fit between practices and abstract concepts. A closer look at situational action itself may be warranted on both technical and political grounds. The case of federal government administration of the public domain in the early 19th century reveals interpretation and discretionary action on the part of field personnel involved in land survey and sales, and clarifies the relationship between concepts and action s in administrative situations. The author argues that the experiential expertise developed in practice is not only an important coping resource but also supports democratic administration. - Reproduced.
Keywords: Democratization; Public administration